A multi-method approach to drafting candidate entrustable professional activities for a general internal medicine residency programme - Matteo Monti; Valérie Pittet; Sonia Frick; David Gachoud (Swiss Medical Weekly)
INTRODUCTION: Entrustable professional activities (EPAs) are units of concrete daily clinical tasks that trainee physicians should be able to handle with increasing autonomy during their postgraduate training. EPAs are gaining international recognition as an essential component of competency-based medical training programmes. The process of developing EPAs for a nationwide training programme is complex and requires an in-depth understanding of EPAs as a concept and good knowledge of appropriate development processes. This article provides a detailed description of the methodology and results of a multi-step approach for developing a list of candidate EPAs for Switzerland’s postgraduate training programme in general internal medicine (GIM).